Literacy and Numeracy Teaching and Learning in Pandemic Outbreak: A Case Study of Private Primary School in Rural Area - Yulia, Yuyun; Ishak, Wan Irham; Perbowo, Krisna Satrio; Widodo, Sri Adi (FKIP Universitas Lampung, 2023)
Literacy and Numeracy Teaching and Learning in Pandemic Outbreak: A Case Study of Private Primary School in Rural Area. Objective: This research aims to portray the teaching and learning of literacy and numeracy in a private school in rural area with few students in each class. Methods: The research method employed is descriptive qualitative. Data revealed that students doing Kampus Mengajar Angkatan 1 (KMA-1) or student teacher taught literacy and numeracy lesson through playing games and singing. Finding: The teaching procedures are claimed in three phases – pre, while and post. The teaching and learning process during the pandemic was carried out in various ways such as using videos and using games and singing. Conclusion: Students’ challenges are lack of vocabulary and its meaning. To conclude, teachers need to develop their teaching and learning based on student and school characteristics. This is done to develop student learning motivation, literacy, and student numeracy can improve Keywords: literacy, numeracy, rural area, private primary school, kampus mengajar angkatan 1DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202301